The evaluation framework for Malaysian services success in mobile government environment - Noor Dheyaa Azeez (2019)
The purpose of this study was to develop the M-government service success evaluationframework (M-GSEF) to evaluate mobile-government (M-government) service success fromthe perspective of citizens. The development of the evaluation framework was carried out byexploring the dimensions and factors of M-government service success and adapting DeLoneand McLeans IS success model. A number of dimensions and associated factors within eachdimension of the M-GSEF were identified. System quality, information quality, and servicequality were the dimensions adopted from the DeLone and McLean's model, whereasintention to use and user satisfaction were the dimensions re-specified in the proposedframework as citizen's use/usefulness and citizen's satisfaction, respectively. Meanwhile,citizens trust, perceived M-government service quality and perceived effectiveness wereincorporated as new dimensions in the proposed framework. The design of the present studyis based on descriptive research method. This study used a quantitative approach involvingthe Fuzzy Delphi technique and structural equation modeling to evaluate and validate theproposed framework, respectively. Questionnaires were used to collect the data from a samplesize of 380 people from Kuala Lumpur, Perak and Selangor in Malaysia. The findingsdemonstrated strong positive correlation relationships as a following significant valuesbetween perceived M-government service quality with system quality was 0.25; informationquality was 0.20, service quality was 0.16 and citizens satisfaction was 0.13. In addition,citizens trust exhibited direct relationships with perceived M-government service quality andperceived effectiveness of M-government services as their critical ratios (0.19 and 0.30). Thus,as the major contribution of the proposed study is to (1) develop evaluation framework for mgovernmentsuccess through (2) the identified new dimensions, namely, perceived Mgovernmentservice quality, citizens trust and perceived effectiveness, and (3) respecifieddimensions, namely, citizens use/usefulness and citizens satisfaction, have majorsignificance in the success of the M-government myGov service in the context of Malaysiancitizens perspective. Surely, the study has a major implication on the current practice in thatthe proposed framework (M-GSEF) can provide the Malaysian government's agencies withappropriate indicators to evaluate the success of M- government services